2017
DOI: 10.5812/iranjradiol.14384
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Solid Papillary Carcinoma of Male Breast: A Rare Case Report

Abstract: Invasive papillary carcinoma of the breast is a rare form of breast carcinoma. Hereby we report a case of invasive papillary carcinoma of the breast in a 76-year-old otherwise healthy male, who presented at our department with the complaint of left subareolar masses. Mammography demonstrated two masses that were oval and round shaped, sharply demarcated and with micro calcifications on the internal structure. Ultrasonographic (US) analysis revealed solid mass lesions in the left subareolar location. These lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…The data that support the findings of this study are openly available in PubMed at "http:// doi.org/[doi]," reference number [1,[3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Statement Of Ethicsmentioning
confidence: 61%
See 1 more Smart Citation
“…The data that support the findings of this study are openly available in PubMed at "http:// doi.org/[doi]," reference number [1,[3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Statement Of Ethicsmentioning
confidence: 61%
“…Additionally, we checked case reports, clinical SPC studies, and the references cited in the original articles, excluding some articles whereby the authors confirmed other papillary neoplasms. Eleven male SPC cases have been identified, including our case [1,7,[9][10][11][12][13][14][15] (Table 1). These patients were relatively older, and most had a palpable mass.…”
Section: Case Reports In Oncologymentioning
confidence: 99%
“…In papillary carcinoma fibrovascular stroma is less conspicuous due to pronounced epithelial component proliferate in discontinuous fashion and have hyperchromatic nuclei, high nucleocytoplasmic ratio and variable mitotic figures [12] .Treatment of invasive papillary carcinoma varies according to staging and presence of hormone receptors. Lumpectomy and mastectomy is followed byadjuvant chemotherapy, radiotherapy and hormone therapy [13] . In our patient after mastectomy patient had undergone chemotherapy and radiotherapy and patient is doing well now.…”
Section: Discussionmentioning
confidence: 99%